1994
DOI: 10.1161/01.cir.89.6.2519
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in serum cholesterol with pravastatin improves endothelium-dependent coronary vasomotion in patients with hypercholesterolemia.

Abstract: BACKGROUND This study aimed to determine if cholesterol-lowering therapy improves endothelium-dependent coronary vasomotion in patients with hypercholesterolemia. METHODS AND RESULTS Nine patients with hypercholesterolemia were studied before and after cholesterol-lowering therapy with pravastatin (an inhibitor of HMG-CoA reductase) for 6 +/- 3 months, which lowered serum cholesterol from 272 +/- 8 to 187 +/- 16 mg/dL (P < .01). Control patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
226
3
14

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 558 publications
(249 citation statements)
references
References 25 publications
6
226
3
14
Order By: Relevance
“…[8][9][10][11][12]28 Furthermore, in patients with hypercholesterolaemia, radial artery compliance was found to increase to a larger extent after a two-year treatment than after a six-month treatment of simvastatin. 15,29 Finally, all these findings taken together agree with the clinical observations that, although favourable changes in lesion composition were observed within three months of statin treatment, clinical trials suggest that event reduction takes six-twelve months after initiation of treatment.…”
Section: Commentsmentioning
confidence: 92%
See 1 more Smart Citation
“…[8][9][10][11][12]28 Furthermore, in patients with hypercholesterolaemia, radial artery compliance was found to increase to a larger extent after a two-year treatment than after a six-month treatment of simvastatin. 15,29 Finally, all these findings taken together agree with the clinical observations that, although favourable changes in lesion composition were observed within three months of statin treatment, clinical trials suggest that event reduction takes six-twelve months after initiation of treatment.…”
Section: Commentsmentioning
confidence: 92%
“…[4][5][6][7] Subsequently, lipid-lowering agents may have various consequences on arterial stiffness. First, statins are known to have a beneficial effect on endothelial function, thereby restoring nitric oxide (NO) bio-activity in atherosclerotic populations 8,9 and thus producing an NO-induced large artery dilatation and reduction of stiffness. 3 Secondly, statins cause, at an early phase, a rapid reduction of lipid vascular content, and thereby may be responsible for an absolute or relative increase in collagen, a process causing an increase of arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, statin therapy may support one of the fundamental survival responses to maintain tissue viability in the face of acute or chronic myocardial ischemia in patients with obstructive coronary artery disease. [22][23][24] We have shown that an improvement in lipid profile could be considered to be another factor for the improvement of endothelial function in the coronary artery. Recently, Sakabe et al 25 reported that atorvastatin therapy has some beneficial effects within 2 weeks, including effects on LDL subfraction distribution and remnant-like particle-cholesterol (RLP-C), antioxidant effects, and alterations in endothelial function of the brachial artery, which may be important in the treatment of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, coronary atherosclerosis and hypercholesterolaemia have also been associated with dysfunction of endothelium-mediated vasomotion, which impairs coronary or myocardial blood flow and forearm blood flow [123][124][125][126]. Lipid-lowering therapy has shown to improve the endothelium medi ated vasomotion after relative short periods of time [127][128][129]. For example, Egashira et al [127] demonstrated a significant improvement in coronary blood flow in response to acetylcholine infusion in patients with hypercholesterolaemia and pravastatin therapy.…”
Section: Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…Lipid-lowering therapy has shown to improve the endothelium medi ated vasomotion after relative short periods of time [127][128][129]. For example, Egashira et al [127] demonstrated a significant improvement in coronary blood flow in response to acetylcholine infusion in patients with hypercholesterolaemia and pravastatin therapy. Anderson et al [130] showed recently that the addition of antioxidant therapy with probucol to cholesterol-lowering treatment with lovastatin im proved acetylcholine-induced, endothelium-depen dent vasodilation significantly more than cholesterol lowering alone.…”
Section: Endothelial Cell Dysfunctionmentioning
confidence: 99%